Rethinking Latin American development and its link with neoliberalism: a Foucauldian analysis of the beginnings of the G77 - González-Hernández, Ayleen Dicklodina (The University of Edinburgh, 2017)
Nowadays, the G77 is a key factor in North-South negotiations at the UN to achieve global commitments. On the understanding that neoliberalism is an economic rationale that strongly influences the relationship between North and South, this research explores the influence of a primordial neoliberalism in Latin American interest in taking part in the G77 at the First United Nations Conference on Trade and Development (UNCTAD). Utilising the ideas of Michel Foucault to analyse discourses of the Economic Commission for Latin America (ECLA) since its incorporation into the G77 establishment, this work claims that the neoliberal rationale in part lies behind the mechanism that leads Latin American countries to take part in the G77 at the UNCTAD I. This mechanism is the need for development and the consequent concept of “developing country” reinforced by the G77 at the UN negotiations. In particular, the lack of natural resources in international markets due to the world wars produced the need for surveillance of non-industrialised countries. This surveillance, called here “Police of Development”, was supported by knowledge of natural resources provided by the ECLA, and reinforced the differentiation of countries. This differentiation promoted the need for industrialisation and the need for development. Thus, in a context of lack of financing and deterioration of the international terms of trade of natural resources, Latin Americans seeking development present themselves as “developing” countries in their international negotiations through the G77. The idea of development encourages the production and export of natural resources, which is necessary for a continuous availability of raw materials in international trade to maintain the expansion of markets, a basic precept of neoliberalism.
Keywords: development; neoliberalism; Latin America; Foucault; United Nations; G77; UNCTAD